2020
DOI: 10.3345/kjp.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Placental histopathology in late preterm infants: clinical implications

Abstract: Background: The etiopathogenesis of late preterm (LPT) birth is undetermined. Placental histopathology, which reflects an adverse intrauterine environment and is reportedly associated with preterm labor and neonatal morbidities, has not been studied in LPT infants.Purpose: We investigated placental pathological lesion as markers of an adverse intrauterine environment during LPT labor.Methods: This retrospective case-control study compared placental histopathological and clinical variables between LPT and term … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…In a study, the authors were not found any difference between the late preterm and term pregnancies for placental pathologies. (17). Yin et al (18) examined placentas after birth and found that this grading in term placentas did not reflect the functional capacity of the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…In a study, the authors were not found any difference between the late preterm and term pregnancies for placental pathologies. (17). Yin et al (18) examined placentas after birth and found that this grading in term placentas did not reflect the functional capacity of the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…The need for standardisation arises because common placental histopathological lesions are seen in PTB cases with and without infection. These include: villitis of unknown origin (destructive villous inflammatory lesion), acute or chronic chorioamnionitis (inflammation of chorioamnionic membrane), and chronic deciduitis (inflammation of decidua basalis) [ 12 15 ].…”
Section: Introductionmentioning
confidence: 99%